O programa Rede de Escolas Associadas da Unesco e suas implicações na gestão administrativa e pedagógica da escola: estudo de caso em uma escola de educação infantil da rede municipal de Santa Maria/RS - Machado, Sabrina Magrini Peixoto (2020)
This dissertation, developed in the Course of Professional Master Graduation Course of Public Politics and Educational Management has as general objective analysing the impact of the program Net of Associated Schools of the Organization of the United Nations for Education, Science and Culture (UNESCO) in the management of a Children Education School of the City Net in Santa Maria–RS. Theoretical foundation was based on studies of authors Rosemberg (2002), Flores and Susin (2013), Peroni (2012), Chizotti (2006), Imbernon (2010), Vieira (2011), Campos et al (2011), Campos (2012), Yin (2001) and Flick (2013), as well as on the work of other scholars related to the theme. The realization of this study of case counted firstly with content analysis (Bardin, 2016) of electronic correspondences and projects of the school related to the program UNESCO Net of Associated Schools. The second stage counted with the participation of teachers of the school, the manager of the institution and a representative of the municipal education department who answered to questionnaires and interviews related to the certification process and the acting of the school program. After analyzing the documents and the collected data we realized that the Net of Associated Schools of UNESCO acts influencing ideas from the perspective of UNESCO themes, focusing on world peace, education for sustainability, human rights, world problems and the United Nations role. Besides, the program encourages collaborative learning and the search for partnerships for the projects. Nevertheless, the verified lack of financial support from the program is a great obstacle for the enlargement of the school’s actions, as well as the proposal of creating an educator network doesn’t therefore guarantee the union of the schools and the partnership among them for realization of the projects, which relegates them the task of searching partnership and disseminating the ideas of UNESCO for the community. The suggestion of the program of creating partnership between public schools and private enterprises threatens the democratic relation and the school’s autonomy. Viewing the conclusion of the study, the realization of an action plan for the schools of Santa Maria certified in the program was defined. This plan focuses on the formation of a commission of associated schools of the city; the realization of a continuous formation on the axes of the program focused on local actions and the creation of a site of PEA-UNESCO School Net of Santa Maria. Thus, the aim is to create room for dialogue between schools and the coordinators of the program to meet the demand evidenced by the researched school and enable a more critical reflection on the themes of the program and its objectives.